Improving Performance Through Strengthening Discipline and Leadership Role - Zainuri (Indonesian Journal of Society Development, 2023)
This research aims to determine performance through strengthening discipline and the role of performance leadership at KSN (National Gymnastics Community) Durentiga sub-district, Pancoran sub-district, South Jakarta. The research method uses a quantitative approach, primary data, secondary data on personnel, data using a number of KSN members as many as 17 people. The data collection mechanism is by interview, questionnaire instrument. The survey instrument was delivered to KSN members. Data analysis using the SPSS model to test the significance of leadership and work discipline influencing performance. The research results show that leadership and work discipline have a significant positive effect on a person's performance, both partially and simultaneously. Leadership is the most important factor influencing employee performance. In an organization, leaders must continue to develop a good organizational culture and be in line with work discipline for employees to achieve the best performance